A Study on the Performance and Risk-Return Characteristics of Hedge Funds - Guleria, Arjun (2008)
There has been an exponential rise in the number of hedge funds in the recent past as well as an increasing use of hedge funds as a part of investment portfolios since they seem to provide significant diversification benefits. As they are not formally organized or regulated like other investment companies, they have the liberty to pursue unconventional investment strategies including for example, heavy use of derivatives, short sales and leverage and as a result they are often responsible for unpredictable swings in the market While hedge fund investment strategies are often shrouded by secrecy, this paper attempts to analyse the performance of hedge funds, as well as their unique risk and return characteristics. We further aim to analyse the possible diversification benefits of hedge funds as returns on hedge funds often have a low correlation with other financial assets and they also supposedly offer a higher return for comparatively lower risk. Thus we will investigate its unique characteristics and its relation with the S&P 500 index through various quantitative tools like linear regression analysis, performance ratios and correlation analysis of the different strategies with the market. Our results do show evidence of value added by Hedge Funds, and find them beneficial in portfolios as well in a mean-variance framework. The results does show majority of the strategies to posses the unique and dynamic characteristics as expected from previous research but the biases and other problems discussed below do make the conclusions less objective.